1998
DOI: 10.1136/thx.53.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognosis of life time non-smokers with severe alpha 1-antitrypsin deficiency

Abstract: Background-The hereditary disorder 1 -antitrypsin deficiency is characterised by development of severe emphysema at an early age with smoking being the most significant additional risk factor. The purpose of the present paper was to analyse potential risk factors other than smoking for emphysema and to estimate the prognosis of life time non-smokers. Methods-Patientswere identified through the files of the Danish 1 -antitrypsin deficiency register which contains information on more than 700 persons with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 19 publications
4
34
1
3
Order By: Relevance
“…Case reports have shown that bronchiectasis occurs in some persons with the Pi-ZZ phenotype (severe deficiency), but there were alternative causes for bronchiectasis in many of these cases, and thorough exclusion of other causes was not always performed (33). Our findings of no Pi-ZZ persons and no significant increase in the frequency of partial deficiency phenotypes (Pi-MS and Pi-MZ) fail to support any role for ␣ 1 -antitrypsin deficiency in the etiology of bronchiectasis and is in keeping with some previous studies (31,34).…”
Section: Discussionsupporting
confidence: 73%
“…Case reports have shown that bronchiectasis occurs in some persons with the Pi-ZZ phenotype (severe deficiency), but there were alternative causes for bronchiectasis in many of these cases, and thorough exclusion of other causes was not always performed (33). Our findings of no Pi-ZZ persons and no significant increase in the frequency of partial deficiency phenotypes (Pi-MS and Pi-MZ) fail to support any role for ␣ 1 -antitrypsin deficiency in the etiology of bronchiectasis and is in keeping with some previous studies (31,34).…”
Section: Discussionsupporting
confidence: 73%
“…Some alpha-1 antitrypsin-deficient smokers never develop obstruction (25). Some families appear to have an increased risk of COPD and it is probable that other genetic factors may increase susceptibility to COPD (26).…”
Section: Epidemiologymentioning
confidence: 99%
“…A subgroup of COPD patients has an inherited PiZZ (Glu342Lys) alpha-1 antitrypsin deficiency (A1ATD), which is a genetic risk factor for early-onset emphysematous COPD [10]. In the recent literature, solely the Canadian Thoracic Society recommends PR particularly for patients with A1ATD-related COPD [11].…”
Section: Introductionmentioning
confidence: 99%